Perioperative intranasal dexmedetomidine for the prevention of chronic postsurgical pain following thoracoscopic surgery: protocol for a multicentre randomised controlled trial - Yuelun Zhang; Le Xu; Lu Che; Le Shen (BMJ Open)
Introduction Chronic postsurgical pain (CPSP) is common among patients undergoing thoracic surgery, with an incidence of up to 43.99% even with video-assisted thoracoscopic surgery (VATS). CPSP is associated with prolonged opioid use and significantly reduced quality of life. Currently, there are no consistently effective preventive measures. Poor perioperative sleep quality has been increasingly recognised as a key contributing factor to CPSP. Therefore, improving perioperative sleep quality is a potentially modifiable factor in the prevention of CPSP. Dexmedetomidine, an α2-adrenergic receptor agonist, has been shown to improve sleep quality in various patient populations. However, direct evidence supporting its role in reducing the incidence of CPSP is lacking. The aim of this multicentre randomised controlled trial is to investigate the efficacy of perioperative intranasal dexmedetomidine to optimise sleep and reduce the incidence of CPSP.Methods and analysis This prospective, randomised controlled trial will enrol 364 patients undergoing elective VATS. Eligible patients who meet the inclusion and exclusion criteria will be randomly assigned to either the dexmedetomidine group or the control group. Patients in the dexmedetomidine group will receive perioperative intranasal dexmedetomidine spray, while those in the control group will receive an equivalent volume of intranasal normal saline. Assessments will be conducted at baseline, on postoperative days 1, 2 and 3, and at 1, 3 and 6 months after surgery. The primary outcome is CPSP at 3 months postoperatively. Secondary outcomes include sleep quality, emotional status, pain intensity and opioid consumption.Ethics and dissemination The study protocol was approved by the Peking Union Medical College Hospital Institutional Review Board (Ethics Review Committee No. I-25PJ0337) on 7 February 2025. The trial was registered on ClinicalTrials.gov on 16 March 2025, in accordance with ICMJE guidelines. The results will be published in academic journals and disseminated at research conferences.Trial registration number NCT06849466.